2023
DOI: 10.3390/ejihpe13040055
|View full text |Cite
|
Sign up to set email alerts
|

Muscular and Prefrontal Cortex Activity during Dual-Task Performing in Young Adults

Abstract: Postural control depends on attentional resources besides automatic processes. The dual-task paradigm is a possible approach to analyzing the interference and performance between motor and/or cognitive tasks. Various studies showed that, when individuals simultaneously perform two tasks, the postural stability can decline during a dual-task compared with a single-task due to the attentional resources required performing the tasks. However, little is known about the cortical and muscular activity pattern during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In this line, our results may indicate that with a decrease in muscle activity during a dual task, young adults may be less prepared to react to external perturbations due to the inadequate division of the cognitive resources available between cognitive tasks on a smartphone and maintaining a standing position. Furthermore, a previous study showed increased prefrontal cortex activity during dual tasking in young adults, demonstrating a prioritization of the cognitive task to the detriment of motor performance [25].…”
Section: Discussionmentioning
confidence: 82%
“…In this line, our results may indicate that with a decrease in muscle activity during a dual task, young adults may be less prepared to react to external perturbations due to the inadequate division of the cognitive resources available between cognitive tasks on a smartphone and maintaining a standing position. Furthermore, a previous study showed increased prefrontal cortex activity during dual tasking in young adults, demonstrating a prioritization of the cognitive task to the detriment of motor performance [25].…”
Section: Discussionmentioning
confidence: 82%